Evolution of Information Technology in Educational Management - O'Mahony, Christopher; Finegan, Andrew; Visscher, Adrie J.; Tatnall, Arthur; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
International Federation for Information Processing The IFIP series publishes state-of-the-art results in the sciences and technologies of information and communication. The scope of the series includes: foundations of computer science; software theory and practice; education; computer applications in technology; communication systems; systems modeling and optimization; information systems; computers and society; computer systems technology; security and protection in information processing systems; artificial intelligence; and human-computer interaction. Proceedings and post-proceedings of refereed international conferences in computer science and interdisciplinary fields are featured. These results often precede journal publication and represent the most current research. The principal aim of the IFIP series is to encourage education and the dissemination and exchange of information about all aspects of computing. For more information about the 300 other books in the IFIP series, please visit www.springer.com. For more information about IFIP, please visit www.ifip.org.
Bringing Order into Chaos: Building an Integrated School Management Information System - A Case Study from Germany -- ITEM Strategic Planning: Two Approaches -- University Web Portals: Patterns and Policies -- ITEM out of WG 3.7: Is there any life out there? -- E-Contents for Technological Literacy in a Pre-College Program -- On the Utilization of a New Class of School Information Systems: School Performance Feedback Systems -- First no Choice, then Some Choice, and Finally Overload: A Reasonable Data Management Evolution? -- Information Technology for Educational Management at a Ugandan Public University -- A New Perspective on Competency Management: Implemented Through Effective Human-Computer Interaction -- Students' Inquiry Learning in the Web 2.0 Age -- How and Why Finnish Universities of Applied Sciences Defined a New Approach to Build a Next Generation Student and Study Management System -- The Role of the School MIS in Pupil Transfer Within England -- Research Management Systems as an Evolutionary Backwater: A Management System for Australian University Research Quality Framework Data -- Evolving Forms of Visualisation for Presenting and Viewing Data -- Industry-Based Learning -- The Future of School Performance Feedback Systems: Conference Discussion Group Paper -- ITEM Evolution: Conference Discussion Group Paper -- Requirements of University ITEM Systems: Conference Discussion Group Paper.
Keywords: COMPUTER SCIENCE; EDUCATION; INFORMATION SYSTEMS; COMPUTER SCIENCE; USER INTERFACES AND HUMAN COMPUTER INTERACTION; MANAGEMENT OF COMPUTING AND INFORMATION SYSTEMS; COMPUTERS AND EDUCATION